Celso Furtado: fundação e prospectiva do desenvolvimento - Candido Mendes (Universidade do Estado do Rio de Janeiro, 2005)
The article analyzes the political and intellectual career of Brazilian economist Celso Furtado, who passed away in November 2004. The author highlights Furtado's decisive role in the construction of relevant public institutions for the country and his original reflections on Brazilian economic thinking and the issue of underdevelopment.